Building Bridges: The Critical Role Of Financial Literacy In A Tech-Driven Inclusive Finance Landscape - Sumera Mehmood , Quratulain Siddiq , Khuram Nabi Shaikh, Muhammad Asif Khan , Abdur Rahman Aleemi (Migration Letters, 2024)
Purpose The literature survey will investigate the part of technical capital in building a literature inclusive financial system with financial literacy as a control variable. By reviewing contemporary academic sources, the survey analyzes focus topics, drivers and illustrations of the effects of technological improvements on the increasing arrival of financial services. The objective of this research is to delve further into the function of technology in acceleration of financial inclusion and financial literacy as a mediation variable. This investigation’s objective is to explore through the use of latest peer-reviewed studies how the application of technological techniques is one of the causes of the expansion in the availability and the level of financial services and the promotion of financial inclusion. Design This study is adopted a quantitative research design which aims at looking into the impact of technological innovation on financial literacy and inclusive financial participation. The quantitative part is administered by collection of structured data in mass and the preparedness of sample with multiple demographic group and geographic location representation. The surveys gather data on users’ financial inclusion needs which involves amongst many other: the frequency of use of fintech services. Furthermore, the participants’ financial literacy level and experiences with inclusive finance are also collected. Methodology The research methodology utilized in this study features the empirical process identifying and relating to both quantitative The process of data collection happens in two ways: quantitative data is gathered through a carefully planned survey administered to a gender-mixed group of individuals, while qualitative data is gained through the semi-structured interviews with the key stakeholders. Analyzed data is performed through using statistical techniques such as PLS SEM analysis. The study uses PLS-SEM modeling to investigate the impact of the drivers of IF, financial literacy, and financial initiatives on sustainable growth. The results highlight that usage, digitalization, and FinTech emerged as significant drivers of IF. The financial inclusion in regards to technological innovation and the mediating role of financial literacy. Findings The study conducted also renders a number of important revelations on the effects of technological advancement, spread of financial literacy as well as the growth of financial inclusion. Through quantitative research it has been established that technological innovations like mobile banking and digital payments have in fact a decisive role in reducing the “financial service gap” of low-income markets. On the other hand, financial literacy becomes a mediating factor in improving the outcome of inclusive finance program by enabling user finance to make the optimum use of financial technology and to gain access to the wide including financial service products. Implications The findings of the present study carry implications, the significance of which can be recognized by policymakers, practitioners, and researchers in the field of inclusive finance. Policymakers may use this information to shape targeted interventions, as well as inclusive policies, which tackle those factors that hinder from being the part of finance technology (Fintech) family. By blending the study factors, practitioners can use them across their techniques of the delivery courses of financial education and inclusive finance services, so that they are available, relevant, and effective to all. In the long run, these types of studies provide the scientific foundation for sequence development methods of economies with due consideration of measures for providing financial inclusion and poverty reduction.